2021
DOI: 10.3758/s13428-021-01663-w
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and precision of visual and auditory stimulus presentation in virtual reality in Python 2 and 3 environments for human behavior research

Abstract: Virtual reality (VR) is a new methodology for behavioral studies. In such studies, the millisecond accuracy and precision of stimulus presentation are critical for data replicability. Recently, Python, which is a widely used programming language for scientific research, has contributed to reliable accuracy and precision in experimental control. However, little is known about whether modern VR environments have millisecond accuracy and precision for stimulus presentation, since most standard methods in laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…Apparatus and Stimuli. Participants placed their right hand on a table and wore an HMD that displayed visual stimuli in stereoscopic 3D (76). A transparent board was placed over the hand, resting on two blocks (8 cm in height).…”
Section: Methodsmentioning
confidence: 99%
“…Apparatus and Stimuli. Participants placed their right hand on a table and wore an HMD that displayed visual stimuli in stereoscopic 3D (76). A transparent board was placed over the hand, resting on two blocks (8 cm in height).…”
Section: Methodsmentioning
confidence: 99%
“…Data on temporal accuracy for VR headsets are not only scarcer ( Chénéchal & Goldman, 2018 ; Tachibana & Matsumiya, 2021 ; Wiesing, Fink, & Weidner, 2020 ) but also difficult to interpret, as some studies programmed their experiments directly in the Unity or Unreal engines, whereas others used commercial software programs. However, it seems that temporal accuracy with VR headsets is not as good as with CRT monitors.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, when very short auditory and visual stimuli are presented, it is essential for researchers to ensure that their system is capable of delivering such short stimuli. For example, Tachibana and Matsumiya demonstrated that certain systems may not be able to play auditory and visual stimuli with a duration of 22.22 ms or shorter at all [ 24 ]. The accuracy of such short stimuli depends on the frame rate and display refresh rate set by the running software program.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that, while stimulus duration was highly accurate, built-in timing procedures suffered from variable reaction times and inaccurate stimulus onsets. In another study, Tachibana and Matsumiya evaluated the accuracy and precision of visual and auditory stimuli generated in VR head-mounted displays (HMDs) from HTC and Oculus using Vizard on both Python 2 and 3 [ 24 ]. They found an 18 ms time lag for visual stimuli and a 40 − 60 ms time lag for auditory stimuli, with low jitter in the order of 1 ms for visual and 4 ms for auditory.…”
Section: Introductionmentioning
confidence: 99%